Design and synthesis of a potential inhibitor for DEN2 NS2B/NS3 serine protease / Lee Yean Kee - Lee, Yean Kee (2011)
This work involves searching and designing of inhibitors for DEN2 NS2B/NS3 serine protease. It comprises three phases: modeling, synthesis and screening. Homology model construction of DEN2 NS2B/NS3 serine protease was carried out using HCV NS3/NS4A as a template. The model was then evaluated using server-based structural verification from UCLA-DOE Institute for Genomics and Proteomics server (http://nihserver.mbi.ucla.edu/SAVES/) and PROCHECK, VERIFY3D and ERRAT. The results revealed the homology model have reasonable protein fold compared to the crystal structure of DEN2 NS3 without the cofactor of NS2B bound within. The work then continued with in silico protein-ligand docking experiment using AUTODOCK 3.05, where the homology model was used as the macromolecule and the ligands were the competitive inhibitor (4-hydroxypanduratin A, panduratin A and ethyl 3-(4- (hydroxymethyl)-2-methoxy-5-nitrophenoxy)propanoate). The docking results suggested several putative binding informations for each of the ligand tested, when the detail binding interactions between the enzyme and the ligands were carried out. Based on these informations, a novel ligand was designed with better in silico binding energy. This ligand was then synthesised in convergent approach by employing 1,4- dihydopyridine synthesis, Michael addition and Grignard reaction as the key steps. The screening was performed using the synthesised product on the DEN2 NS2B/NS3 serine protease recombinant and the result seemed to indicate the compound to exhibit uncompetitive inhibition mode.